(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The experiment was conducted to evaluate the effects of growth promoter (Aviator™) and enzymes (Acinor™) with basal feed. A total of 40 Cobb-500 Broiler day old chicks were reared in an open sided gable type house for a period of 5 weeks from 24th september to 28th october, 2017. Body weight and feed intake were recorded on day 0, 7, 14, 21, 28 and 35. The experiment was conducted in a Completely Randomized Design (CRD). Birds were randomly distributed into four dietary groups i.e control (T0) with basal diet, T1 with basal diet and growth promoter (GP) @ 2 gm/kg of feed; T2 with basal diet and enzymes (EZ) @ 0.4 gm/kg of feed and T3 with basal diet and GP plus EZ (2 gm/kg + 0.4 gm/kg). The records were kept on body weight, feed intake and mortality while weight gain, feed conversion ratio (FCR) and survivability were calculated. Broiler chicks that received GP and a combination of GP+EZ treatments showed significant improvement in performance (p<0.05) over control with respect to body weight gain, feed conversion ratio, carcass yield. Cost-effectiveness of GP+EZ treatment higher than all other treatments but GP and EZ had almost similar cost-effectiveness. Feeding EZ alone had comparatively less weight gain and almost similar feed conversion ratio compared with GP groups but it’s performance was significantly better than that of control group. This study indicated that the diet containing GP+EZ offered slightly increased benefits to the growth performance of broilers and these benefits were almost equal to the GP. It is revealed that growth promoter (Aviator™) supplementation with enzymes (Acinor™) is beneficial for broiler production. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 59-66